ANALISIS PENGARUH DER, ROA, LDR DAN TATO TERHADAP HARGA SAHAM PADA PERUSAHAAN PERBANKAN - Khasanah, Uswatun; Titiek Suwarti (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Stock prices can fluctuate, this happens because of the mechanism of demand and supply between stock buyers and stock sellers on the stock exchange. This study aims to analyze the factors that influence stock prices, namely DER, ROA, LDR and TATO. This research was conducted on banking companies listed on the IDX from 2017 to 2020. The sampling method used the purposive sampling method with a sample of 36 banks. Test to see the effect using multiple linear regression analysis. The results showed that DER had a significant positive effect on stock prices. ROA has a significant positive effect on stock prices. LDR has a significant positive effect on stock prices and TATO has a significant positive effect on stock prices. The magnitude of the influence of each variable is greatest in the ROA variable of 21982.831, followed by the TATO variable 13101.994, LDR 581.380 and the smallest variable DER 96.568. Adjusted R Square value of 0.439 or 43.9% means that the variables DER, ROA, LDR and TATO are able to provide an overview of stock price changes of 43.9% and the remaining 56.1% is influenced by other variables outside the study.